A proinvasive role for the Ca2+‐activated K+ channel KCa3.1 in malignant glioma. Issue 6 (2nd March 2014) - Turner, Kathryn L.; Honasoge, Avinash; Robert, Stephanie M.; McFerrin, Michael M.; Sontheimer, Harald
Main Points Using the NCI database, we found that upregulation of KCa3.1 correlates with poor prognosis in patients. Pharmacological inhibition or genetic knockdown of KCa3.1 decreases glioma migration, as investigated in vitro and in situ in multiple glioma cell types, including patient‐derived xenograft‐propagated tumors. Glioma invasion is also attenuated by shRNA knockdown of KCa3.1 in tumor cells implanted in mice in vivo.